Dashboard Untuk Visualisasi Penjualan Voucher Pulsa Elektrik Di Rajawali Reload Mojokerto - Khatulistiwa, Angga; Setyawan, Henry Bambang; Sukmaaji, Anjik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Rajawali Reload is one of the suppliers of telephone vouchers are electrically in the Mojokerto and Lamongan. Rajawali Reload parties have difficulty in monitoring the sales target has been set. At this time monitoring of sales achievement has no warning when a sale happens very low, which is now the information is disseminated orally by accounting. Accounting also has a duty to report the achievement of customer sales to the owner, which the report was still in the form of data tables, and should be done first recap thus requiring additional time. Based on the above, it was built dashboards that can display a visualization of the sales voucher electrical pulses. Views are presented in the form of a voucher provider by categori sales, sales voucher which contribute in demand, sales by customer, sales based cluster, target of achieving sales and the target deposit. Results of the system making this dashboard can display information related to the voucher sales target in the form of electrical pulses to the visualization of information and can help owners Rajawali Reload in monitoring the performance of the sales voucher electrical pulses based on the Key Performance Indicator (KPI) set by Rajawali Reload Keywords: Visualization of Information, Dashboard, Sales Monitoring